Analisis Penggunaan Fitur Shopee Paylater Dalam Perspektif Ekonomi Islam (Studi Kasus Mahasiswa Perbankan Syariah FAI UMSU) - M. Rizki Ramadani; Cinta Widya Riska (Yayasan Rahmat Islamiyah, 2023)
This research is a field research (field search), namely research that is directly related to the object under study. The research technique used in this research is a purposive sampling technique. The type of approach in this research is descriptive qualitative research. Where this research was conducted to determine the analysis of the use of Shopee PayLater on Islamic Banking Students FAI UMSU according to an Islamic economic perspective. The results of the study show that an analysis of the use of Shopee PayLater for students is used for: (1) The convenience of the Shopee Paylater system results in students shopping only to buy items they want/attract attention, (2) They feel satisfied with the services provided and the influence from the environment and advertisements for the benefits of using Shopee PayLater services that make them tempted by discounts/promos, (3) Providing a sufficiently large loan limit for a student makes them buy goods only to increase their confidence and lifestyle, (4) Provisions on related Shopee PayLater the loan repayment period is very convenient so that with minimal income, students are free to shop without regard to financial conditions. Since using Shopee PayLater, there has been an increase in consumption by students, causing students to have consumptive behavior. This is done because the Shopee PayLater system